At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Vamos resolver cada problema detalhadamente.
### Questão 7
A expressão numérica é [tex]\(81^{\frac{1}{2}} + 32^{\frac{1}{5}}\)[/tex].
1. Vamos primeiro calcular [tex]\(81^{\frac{1}{2}}\)[/tex]:
- O expoente fracionário [tex]\(\frac{1}{2}\)[/tex] representa a raiz quadrada.
- [tex]\(81^{\frac{1}{2}}\)[/tex] é a raiz quadrada de 81.
[tex]\[ \sqrt{81} = 9 \][/tex]
2. Agora, vamos calcular [tex]\(32^{\frac{1}{5}}\)[/tex]:
- O expoente fracionário [tex]\(\frac{1}{5}\)[/tex] representa a raiz quinta.
- [tex]\(32^{\frac{1}{5}}\)[/tex] é a raiz quinta de 32.
[tex]\[ \sqrt[5]{32} = 2 \][/tex]
3. Somando esses valores:
[tex]\[ 9 + 2 = 11 \][/tex]
Portanto, o valor da expressão numérica [tex]\(81^{\frac{1}{2}} + 32^{\frac{1}{5}}\)[/tex] é:
[tex]\[ \boxed{11} \][/tex]
### Questão 8
Queremos calcular o valor de [tex]\(x + y\)[/tex], dadas as equações:
1. [tex]\(\sqrt{2} + x = 4 \sqrt{2}\)[/tex]
2. [tex]\(\sqrt{3} \cdot y = 5 \sqrt{6}\)[/tex]
Vamos resolver cada equação separadamente.
#### Para [tex]\(x\)[/tex]:
1. Começamos com a equação [tex]\(\sqrt{2} + x = 4 \sqrt{2}\)[/tex].
2. Isolamos [tex]\(x\)[/tex]:
[tex]\[ x = 4 \sqrt{2} - \sqrt{2} \][/tex]
3. Simplificamos subtraindo [tex]\(\sqrt{2}\)[/tex] de [tex]\(4 \sqrt{2}\)[/tex]:
[tex]\[ x = (4 - 1) \sqrt{2} = 3 \sqrt{2} \][/tex]
Portanto, temos [tex]\(x = 3 \sqrt{2}\)[/tex].
#### Para [tex]\(y\)[/tex]:
1. Começamos com a equação [tex]\(\sqrt{3} \cdot y = 5 \sqrt{6}\)[/tex].
2. Isolamos [tex]\(y\)[/tex]:
[tex]\[ y = \frac{5 \sqrt{6}}{\sqrt{3}} \][/tex]
3. Simplificamos a fração. Sabemos que [tex]\(\sqrt{6} = \sqrt{3 \cdot 2}\)[/tex], então:
[tex]\[ y = \frac{5 \sqrt{3 \cdot 2}}{\sqrt{3}} = \frac{5 \sqrt{3} \cdot \sqrt{2}}{\sqrt{3}} \][/tex]
4. Cancelamos [tex]\(\sqrt{3}\)[/tex] no numerador e denominador:
[tex]\[ y = 5 \sqrt{2} \][/tex]
Portanto, temos [tex]\(y = 5 \sqrt{2}\)[/tex].
Agora somamos os valores de [tex]\(x\)[/tex] e [tex]\(y\)[/tex] para encontrar [tex]\(x + y\)[/tex]:
[tex]\[ x + y = 3 \sqrt{2} + 5 \sqrt{2} = 8 \sqrt{2} \][/tex]
Portanto, o valor de [tex]\(x + y\)[/tex] é:
[tex]\[ \boxed{8 \sqrt{2}} \][/tex]
### Questão 7
A expressão numérica é [tex]\(81^{\frac{1}{2}} + 32^{\frac{1}{5}}\)[/tex].
1. Vamos primeiro calcular [tex]\(81^{\frac{1}{2}}\)[/tex]:
- O expoente fracionário [tex]\(\frac{1}{2}\)[/tex] representa a raiz quadrada.
- [tex]\(81^{\frac{1}{2}}\)[/tex] é a raiz quadrada de 81.
[tex]\[ \sqrt{81} = 9 \][/tex]
2. Agora, vamos calcular [tex]\(32^{\frac{1}{5}}\)[/tex]:
- O expoente fracionário [tex]\(\frac{1}{5}\)[/tex] representa a raiz quinta.
- [tex]\(32^{\frac{1}{5}}\)[/tex] é a raiz quinta de 32.
[tex]\[ \sqrt[5]{32} = 2 \][/tex]
3. Somando esses valores:
[tex]\[ 9 + 2 = 11 \][/tex]
Portanto, o valor da expressão numérica [tex]\(81^{\frac{1}{2}} + 32^{\frac{1}{5}}\)[/tex] é:
[tex]\[ \boxed{11} \][/tex]
### Questão 8
Queremos calcular o valor de [tex]\(x + y\)[/tex], dadas as equações:
1. [tex]\(\sqrt{2} + x = 4 \sqrt{2}\)[/tex]
2. [tex]\(\sqrt{3} \cdot y = 5 \sqrt{6}\)[/tex]
Vamos resolver cada equação separadamente.
#### Para [tex]\(x\)[/tex]:
1. Começamos com a equação [tex]\(\sqrt{2} + x = 4 \sqrt{2}\)[/tex].
2. Isolamos [tex]\(x\)[/tex]:
[tex]\[ x = 4 \sqrt{2} - \sqrt{2} \][/tex]
3. Simplificamos subtraindo [tex]\(\sqrt{2}\)[/tex] de [tex]\(4 \sqrt{2}\)[/tex]:
[tex]\[ x = (4 - 1) \sqrt{2} = 3 \sqrt{2} \][/tex]
Portanto, temos [tex]\(x = 3 \sqrt{2}\)[/tex].
#### Para [tex]\(y\)[/tex]:
1. Começamos com a equação [tex]\(\sqrt{3} \cdot y = 5 \sqrt{6}\)[/tex].
2. Isolamos [tex]\(y\)[/tex]:
[tex]\[ y = \frac{5 \sqrt{6}}{\sqrt{3}} \][/tex]
3. Simplificamos a fração. Sabemos que [tex]\(\sqrt{6} = \sqrt{3 \cdot 2}\)[/tex], então:
[tex]\[ y = \frac{5 \sqrt{3 \cdot 2}}{\sqrt{3}} = \frac{5 \sqrt{3} \cdot \sqrt{2}}{\sqrt{3}} \][/tex]
4. Cancelamos [tex]\(\sqrt{3}\)[/tex] no numerador e denominador:
[tex]\[ y = 5 \sqrt{2} \][/tex]
Portanto, temos [tex]\(y = 5 \sqrt{2}\)[/tex].
Agora somamos os valores de [tex]\(x\)[/tex] e [tex]\(y\)[/tex] para encontrar [tex]\(x + y\)[/tex]:
[tex]\[ x + y = 3 \sqrt{2} + 5 \sqrt{2} = 8 \sqrt{2} \][/tex]
Portanto, o valor de [tex]\(x + y\)[/tex] é:
[tex]\[ \boxed{8 \sqrt{2}} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.